Molybdenum carbide, composite, catalyst ink, method for producing molybdenum carbide, and method for producing composite
By controlling the particle structure and composition of molybdenum carbide, the catalyst ink achieves enhanced catalytic performance and conductivity, addressing the limitations of existing production methods and enabling efficient hydrogen generation.
Patent Information
- Application Number
- JP2024521303
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-08-05
- Filing Date
- 2023-08-03
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-08-03
AI Technical Summary
Existing methods for producing molybdenum carbide struggle with controlling particle structure and composition, leading to suboptimal catalytic performance and conductivity, and require severe reaction conditions.
The production of molybdenum carbide with a specific carbon content, crystal structure, and controlled particle size, combined with noble metal or transition metal particles, to form a catalyst ink with enhanced properties.
The resulting molybdenum carbide exhibits improved catalytic performance and conductivity, suitable for applications in water electrolysis and hydrogen generation.
Smart Images

Figure 0007601286000010 
Figure 0007601286000011 
Figure 0007601286000012
Abstract
Description
[Technical field]
[0001] The present invention relates to molybdenum carbide, a composite, a catalyst ink, a method for producing molybdenum carbide, and a method for producing the composite. This application claims priority based on Japanese Patent Application No. 2022-125418, filed on August 5, 2022, the contents of which are incorporated herein by reference. [Background technology]
[0002] Water electrolysis technology is attracting attention as a way to produce hydrogen from water using renewable energy electricity, with the aim of resolving environmental and energy resource issues. Molybdenum carbide (Mo 2 Molybdenum compounds, such as those represented by C), are expected to be materials that have high catalytic activity while being inexpensive and abundant in resources.
[0003] For example, Patent Document 1 describes an electrode for hydrogen generation that includes at least a metal (A) on whose surface the Volmer reaction occurs and a metal (B) on whose surface the Heyrovsky reaction or the Tafel reaction occurs. Patent Document 1 describes that the combination of metal (A) and metal (B) may be a combination of at least one metal selected from the group consisting of molybdenum carbide, molybdenum boride, molybdenum oxide, nickel molybdate, molybdenum sulfide, tungsten carbide, tungsten boride, and tungsten oxide, and at least one metal selected from the group consisting of nickel and cobalt.
[0004] Various methods for producing molybdenum carbide have been proposed. For example, Patent Document 2 discloses a method for producing molybdenum carbide by heating a gaseous compound of heavy metal such as Mo at a temperature between 900° C. and 1400° C. for 200 min. 2 A method is described in which the compound is reacted with reactive carbon having a specific surface area of 1 / g or more. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2001-234380 A [Patent Document 2] Special Publication No. 3-501721 Summary of the Invention [Problem to be solved by the invention]
[0006] However, it is difficult to control the particle structure and composition of the molybdenum carbide by the method described in Patent Document 2. Therefore, there is room for improvement in the catalytic performance and electrical conductivity of the molybdenum carbide. Moreover, the method described in Patent Document 2 requires strict reaction conditions because it is a high-temperature gas-phase reaction.
[0007] The present invention has been made in consideration of the above circumstances, and has an objective of providing molybdenum carbide having a desired particle structure and composition, a catalyst ink containing the molybdenum carbide, a composite of the molybdenum carbide with precious metal particles, or a transition metal or a transition metal compound, a catalyst ink containing the composite, a method for producing molybdenum carbide, and a method for producing the composite. [Means for solving the problem]
[0008] The present invention includes the following aspects. (1) Mo 2 Molybdenum carbide having a C crystal structure and a carbon content of 6% or more relative to the total mass (100% by mass) of the molybdenum carbide. (2) The molybdenum carbide according to (1) above, in which a carbon-derived graphite band G and a diamond band D are present as measured by Raman spectroscopy. (3) The molybdenum carbide according to (2) above, wherein the ratio (G / D) of the carbon-derived graphite band G to the diamond band D is 0.75 or more. (4) The specific surface area measured by the BET method is 10 to 2000 m 2The molybdenum carbide according to any one of (1) to (3) above, wherein the molybdenum carbide has a molecular weight of 1000 or more and a molecular weight of 1000 or more. (5) Median diameter D calculated by dynamic light scattering 50 The molybdenum carbide according to any one of (1) to (4) above, wherein the average particle size is 1000 nm or less. (6) The molybdenum carbide according to any one of (1) to (5) above, having an average crystallite size of 50 nm or less, determined from a peak at 2θ=39.4±0.5° in a profile obtained by X-ray diffraction measurement. (7) A catalyst ink comprising the molybdenum carbide according to any one of (1) to (6) above and a solvent. (8) A composite of noble metal particles having an average particle size of 20 nm or less and the molybdenum carbide according to any one of (1) to (6) above. (9) The composite according to (8) above, wherein the noble metal particles are palladium particles. (10) The complex according to (9) above, wherein the palladium particles contain an aggregate of palladium atoms not having a crystal structure. (11) A catalyst ink comprising the complex according to any one of (8) to (10) above and a solvent. (12) A composite of at least one transition metal species selected from the group consisting of transition metals and transition metal compounds, and the molybdenum carbide according to any one of (1) to (6) above. (13) The composite with molybdenum carbide according to (12) above, wherein the transition metal species is at least one species selected from the group consisting of nickel and nickel compounds. (14) A catalyst ink comprising the complex according to (12) or (13) above and a solvent. (15) A method for producing molybdenum carbide, comprising calcining molybdenum trioxide containing α-crystals having an average crystallite size of 50 nm or less and carbon in the presence of at least one inorganic compound selected from the group consisting of inorganic salts and inorganic hydroxides. (16) The method for producing molybdenum carbide according to (15) above, wherein the inorganic compound is at least one selected from the group consisting of sodium compounds and potassium compounds. (17) A method comprising the steps of: mixing molybdenum carbide with a precious metal solution; The molybdenum carbide is Mo 2 A method for producing a composite having a C crystal structure and a carbon content of 6% or more relative to the total mass (100% by mass) of molybdenum carbide. (18) A method comprising the steps of: mixing molybdenum carbide with a transition metal compound solution; The molybdenum carbide is Mo 2 A method for producing a composite having a C crystal structure and a carbon content of 6% or more relative to the total mass (100% by mass) of molybdenum carbide. Effect of the Invention
[0009] According to the present invention, it is possible to provide molybdenum carbide having a desired particle structure and composition, a catalyst ink containing the molybdenum carbide, a composite of the molybdenum carbide with precious metal particles, or a transition metal or a transition metal compound, a catalyst ink containing the composite, a method for producing molybdenum carbide, and a method for producing the composite. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a schematic diagram showing an example of an apparatus used for producing molybdenum trioxide particles, which are a raw material for the molybdenum disulfide particles according to an embodiment of the composite. [Diagram 2] FIG. 2 is a diagram showing X-ray diffraction (XRD) profiles of the particles obtained in Examples 1 to 3 superimposed on each other. [Diagram 3] 1 shows transmission electron microscope (TEM, JEM-1400, manufactured by JEOL Ltd.) images of each particle obtained in Examples 1 to 3. [Figure 4] 1 is an observation image of the particles of Example 1 obtained with a high-resolution transmission electron microscope (HRTEM, manufactured by JEOL Ltd., JEM-ARM300F). [Diagram 5] FIG. 2 is a diagram showing X-ray diffraction (XRD) profiles of the particles obtained in Examples 4 to 6 and Comparative Examples 4 and 5, superimposed on each other. [Figure 6]1 shows transmission electron microscope (TEM, JEM-1400, manufactured by JEOL Ltd.) images of the particles obtained in Examples 4 and 6. [Figure 7] 1 is an observation image of the particles of Example 4 obtained using a high-resolution transmission electron microscope (HRTEM, manufactured by JEOL Ltd., JEM-ARM300F). [Figure 8] 1 is a HAADF-STEM image (transmission electron image, JEM-ARM300F, manufactured by JEOL Ltd.) of the particles of Example 4. [Figure 9] 1 is an SEI image (secondary electron image, JEM-ARM300F, manufactured by JEOL Ltd.) of a particle of Example 4. [Figure 10] FIG. 1 is a diagram showing X-ray diffraction (XRD) profiles of particles obtained in Example 7 and Comparative Example 6 superimposed on each other. [Figure 11] 1 is a high-resolution transmission electron microscope (HRTEM, JEM-ARM300F, manufactured by JEOL Ltd.) image of the particles obtained in Example 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] <Molybdenum carbide> The molybdenum carbide according to the present embodiment has a crystal structure of Mo 2 The molybdenum carbide has a C crystal structure, and the carbon content relative to the total mass (100 mass%) of the molybdenum carbide is 6% or more.
[0012] In this embodiment, Mo 2 The presence of the C crystal structure can be detected by a diffraction profile obtained by XRD analysis of a sample of molybdenum carbide. 2 The C crystal structure may be either an α crystal or a β crystal, but is preferably an α crystal.
[0013] The molybdenum carbide according to this embodiment has a carbon content of 6% or more, preferably 8% or more, more preferably 10% or more, and even more preferably 15% or more, relative to the total mass (100% by mass) of the molybdenum carbide. When the carbon content is at least the lower limit of the above range, the electrical conductivity of the molybdenum carbide is easily improved.
[0014] In the molybdenum carbide according to this embodiment, the upper limit of the carbon content relative to the total mass (100 mass%) of the molybdenum carbide is not particularly limited, but is preferably 90% or less, more preferably 80% or less, and even more preferably 60% or less. When the carbon content is equal to or less than the upper limit of the above range, the electrical conductivity and catalytic performance of the molybdenum carbide are likely to be improved.
[0015] In this embodiment, the composition analysis of the molybdenum carbide is molybdenum The content can be determined by heated sealed acid decomposition-ICP-AES (inductively coupled plasma atomic emission spectrometry), and the carbon content can be determined by CHN elemental analysis.
[0016] In the molybdenum carbide according to the present embodiment, it is preferable that a carbon-derived graphite band G and a diamond band D are present as measured by Raman spectroscopy. 2 A hybrid structure of C and carbon is preferable. 2 The state of C and carbon is not particularly limited. For example, Mo 2 The state where carbon exists on the surface of C, Mo 2 For example, a C matrix is dotted with carbon domains.
[0017] In this embodiment, the molybdenum carbide has a ratio (G / D) of the graphite band G to the diamond band D of preferably 0.75 or more, more preferably 0.78 or more, and further preferably 0.80 or more. When G / D is equal to or greater than the lower limit of the above range, the defects resulting from the diamond band D are reduced, and the electrical conductivity and catalytic performance of the molybdenum carbide are likely to be improved.
[0018] In this embodiment, the upper limit of the G / D ratio is not particularly limited, but is preferably 2.0 or less, more preferably 1.5 or less, and even more preferably 1.0 or less. When the G / D ratio is equal to or less than the upper limit of the above range, a synergistic effect with the molybdenum carbide is easily exhibited, and the catalytic performance is easily improved.
[0019] In this embodiment, the molybdenum carbide has a specific surface area of 10 to 2000 m as measured by the BET method. 2 / g, and 20 to 1500m 2 / g is more preferable, and 50 to 1500m 2 It is more preferable that the molecular weight is / g. When the specific surface area measured by the BET method is within the above-mentioned preferred range, for example, in the case where molybdenum carbide is used as a catalyst, the number of catalytically active sites can be increased and mass transfer in the reaction system can be facilitated, thereby making it possible to more effectively improve the catalytic efficiency.
[0020] The specific surface area is measured with a specific surface area meter (e.g., BELSORP-mini manufactured by MicrotrackBell), and the surface area per 1 g of the sample measured from the amount of adsorption of nitrogen gas by the BET method (Brunauer-Emmett-Teller method) is defined as the specific surface area (m 2 / g).
[0021] In this embodiment, the molybdenum carbide has a median diameter D calculated by dynamic light scattering. 50 However, it is preferably 1500 nm or less, more preferably 1000 nm or less, and even more preferably 500 nm or less. Median diameter D 50 When the upper limit value of the above-mentioned preferable range or less is satisfied, for example, when molybdenum carbide is used as the catalyst, the catalytic efficiency is easily exhibited more effectively.
[0022] The median diameter D of the molybdenum carbide of the embodiment is determined by dynamic light scattering. 50 For example, it may be 20 nm or more, or 40 nm or more.
[0023] The median diameter D of the molybdenum carbide of the embodiment is determined by dynamic light scattering. 50 An example of the range of the above numerical value may be 20 nm or more and 1500 nm or less, 40 nm or more and 1000 nm or less, or 40 nm or more and 500 nm or less.
[0024] The median diameter D of the molybdenum carbide of the embodiment calculated by dynamic light scattering method 50 can be determined as the particle size at which the volume cumulative percentage is 50% in a particle size distribution measured in a wet state using a dynamic light scattering particle size distribution analyzer (e.g., Nanotrac WaveII manufactured by MicrotracBEL).
[0025] In this embodiment, the molybdenum carbide preferably has an average crystallite size of 50 nm or less, more preferably 45 nm or less, and even more preferably 40 nm or less, determined from the peak at 2θ=39.4±0.5° in a profile obtained by X-ray diffraction measurement. The above average crystallite size is considered to reflect the particle size and shape of the molybdenum carbide particles, and a smaller crystallite size is preferable because it tends to increase catalytically active sites such as interfaces and defects.
[0026] The lower limit of the average crystallite size of the molybdenum carbide, determined from the peak at 2θ=39.4±0.5° in the profile obtained by X-ray diffraction measurement, may be, for example, 1 nm or more, 3 nm or more, 4 nm or more, or 5 nm or more.
[0027] The average crystallite size of the molybdenum carbide of the embodiment can be determined by the following measurement method.
[0028] [Crystallite size measurement] Measurements are performed using an X-ray diffraction apparatus (e.g., SmartLab 9kW, manufactured by Rigaku Corporation), a scintillation counter as a detector, and PDXL2 as analysis software. The measurement method is the 2θ / θ method, and the average crystallite size is calculated using the Scherrer equation from the half-width of the peak that appears at 2θ=39.4±0.5°. The measurement conditions are a scan speed (2θ) of 2.0° / min, a scan range (2θ) of 10 to 70°, a step (2θ) of 0.02°, and no standard width for the apparatus.
[0029] The molybdenum carbide according to the present embodiment has a crystal structure of Mo 2 The molybdenum carbide according to this embodiment has a C crystal structure and contains 6% or more of carbon relative to the total mass (100% by mass) of the molybdenum carbide. Therefore, the molybdenum carbide according to this embodiment has a large specific surface area, good electrical conductivity and catalytic performance, and is particularly useful for use as a water electrolysis catalyst.
[0030] <Method of manufacturing molybdenum carbide> The method for producing molybdenum carbide according to this embodiment includes calcining molybdenum trioxide containing α-crystals having an average crystallite size of 50 nm or less and carbon in the presence of at least one inorganic compound selected from the group consisting of inorganic salts and inorganic hydroxides.
[0031] The at least one inorganic compound is preferably an alkali metal compound, more preferably at least one selected from the group consisting of sodium compounds and potassium compounds, and further preferably at least one selected from the group consisting of KCl, NaCl, and KOH.
[0032] The amount of the at least one inorganic compound is not particularly limited, but is preferably 5% to 1000%, more preferably 10% to 500%, and even more preferably 20% to 200%, based on the mass of molybdenum trioxide and carbon. When the amount of the at least one inorganic compound is within the above preferred range, molybdenum carbide having high electrical conductivity and catalytic activity is easily formed.
[0033] In this embodiment, the at least one inorganic compound functions as a flux and promotes the reaction between molybdenum trioxide and carbon. The flux method is characterized in that it is possible to synthesize an inorganic compound or control the crystal structure or composition at a temperature relatively lower than that of normal firing.
[0034] In the production method according to the present embodiment, the firing temperature is not particularly limited, but is preferably 400 to 1500° C., more preferably 500 to 1000° C., and further preferably 750 to 880° C. When the firing temperature is within the above preferred range, molybdenum carbide having high electrical conductivity and catalytic activity is easily formed.
[0035] In the production method according to this embodiment, the heating time is not particularly limited, but may be any time that allows the reaction to proceed sufficiently, and may be 1 to 48 hours, 2 to 24 hours, or 4 to 12 hours.
[0036] The production method according to this embodiment may include a step of washing the fired product with water after firing molybdenum trioxide and carbon in order to remove the at least one inorganic compound.
[0037] In the manufacturing method according to the present embodiment, the carbon is not particularly limited, and commercially available carbon particles such as carbon black and carbon nanotubes can be used.
[0038] In the manufacturing method according to this embodiment, the molybdenum trioxide powder has a median diameter D of the primary particles determined by dynamic light scattering. 50 is preferably 10 nm or more and 2000 nm or less, more preferably 10 nm or more and 500 nm or less, and further preferably 10 nm or more and 200 nm or less. Primary particle median diameter D 50 When the molybdenum trioxide powder has a median diameter D of 100 to 200 nm, the reactivity of the molybdenum trioxide powder with carbon is likely to be improved. 50 is calculated from the volume-based cumulative particle size distribution measured using, for example, a dynamic light scattering particle size distribution measuring device.
[0039] In this embodiment, the average particle size of the primary particles of the molybdenum trioxide powder refers to the average value of primary particle diameters of 50 randomly selected primary particles when the molybdenum trioxide powder is photographed with a transmission electron microscope (TEM) or a scanning electron microscope (SEM), the major axis (the Feret diameter of the longest observed part) and minor axis (the shorter Feret diameter perpendicular to the Feret diameter of the longest part) of the smallest unit particle (i.e., primary particle) constituting the aggregate in the two-dimensional image are measured, and the average value is taken as the primary particle diameter.
[0040] In this embodiment, the MoO measured by X-ray fluorescence (XRF) is 3 The content is preferably 99.5% by mass or more, more preferably 99.7% by mass or more, and even more preferably 99.9% by mass or more, based on the total detected peak intensity. MoO 3 When the content ratio of is within the above preferred range, by subjecting the molybdenum trioxide powder to a carbonization reaction, it is easy to obtain a high-purity molybdenum carbide that is free from the risk of producing carbides derived from impurities and has good storage stability.
[0041] In this embodiment, the specific surface area of the molybdenum trioxide powder is 10 m because it has good reactivity with carbon. 2 / g or more, and 2 / g or more is more preferable, and 30m 2 / g or more is more preferable. Since this makes it easier to produce molybdenum trioxide powder, 2 / g or less, and 2 / g or less, 2 / g or less.
[0042] In this embodiment, the average crystallite size of α-crystals contained in the crystal structure of molybdenum trioxide is 50 nm or less, preferably 5 nm or more and 50 nm or less, more preferably 5 nm or more and 45 nm or less, even more preferably 10 nm or more and 40 nm or less, and particularly preferably 10 nm or more and 35 nm or less. When the average crystallite size of the α crystals is within the above range, the reactivity of the molybdenum trioxide powder with carbon tends to be better.
[0043] In the present embodiment, the crystal structure of molybdenum trioxide may further include β crystals having an average crystallite size of 50 nm or less. When the crystal structure of molybdenum trioxide includes α crystals and β crystals, the reactivity of the molybdenum trioxide powder with carbon tends to be improved.
[0044] In this embodiment, the average crystallite size of β crystals contained in the crystal structure of molybdenum trioxide is preferably 5 nm or more and 50 nm or less, more preferably 5 nm or more and 45 nm or less, even more preferably 10 nm or more and 40 nm or less, and particularly preferably 10 nm or more and 30 nm or less. When the average crystallite size of the β crystals is within the above preferred range, the reactivity of the molybdenum trioxide powder with carbon tends to be better.
[0045] In this embodiment, the α-crystal structure of molybdenum trioxide is represented by the following formula in a profile obtained by powder X-ray diffraction (XRD) using Cu-Kα radiation as an X-ray source: MoO 3 The α crystal structure can be confirmed by the presence of a peak on the (021) plane (2θ: around 27.32°, No. 166363 (Inorganic Crystal Structure Database, ICSD)) of MoO. The β crystal structure can also ... 3 This can be confirmed by the presence of a peak (2θ: approximately 23.01°, No. 86426 (Inorganic Crystal Structure Database, ICSD)) which is assigned to the (011) plane of the β crystal of the compound.
[0046] In the present embodiment, the molybdenum trioxide powder is characterized by a profile obtained by powder X-ray diffraction (XRD) using Cu-Kα radiation as an X-ray source, which shows MoO 3 The peak intensity attributable to the (011) plane of the β crystal of MoO 3 The ratio of the peak intensity to the peak intensity attributable to the (021) plane of the α crystal (β(011) / α(021)) is preferably 0.1 or more, more preferably 0.2 or more, and even more preferably 0.4 or more. In this embodiment, the molybdenum trioxide particles preferably have a ratio (β(011) / α(021)) of 10.0 or less.
[0047] MoO 3 The peak intensity attributable to the (011) plane of the β crystal of MoO 3 For the peak intensities attributable to the (021) plane of the α crystal, the maximum intensity of the peak is read, and the ratio (β(011) / α(021)) is calculated.
[0048] In this embodiment, the ratio (β(011) / α(021)) of the molybdenum trioxide powder is preferably from 0.1 to 10.0, more preferably from 0.2 to 10.0, and particularly preferably from 0.4 to 10.0.
[0049] In this embodiment, the α-crystal content of the molybdenum trioxide powder is not particularly limited, but may be 20% or more, 50% or more, 70% or more, 80% or more, or 100%.
[0050] MoO 3 In a mixture of α and β crystals of MoO 3 The α crystal content of MoO can be determined from the obtained profile data by the RIR (reference intensity ratio) method. 3 The RIR value of the α crystal of A and MoO 3 Integral intensity I of the (021) plane of the α crystal of (2θ: around 27.32°_No. 166363 (Inorganic Crystal Structure Database, ICSD))A , and MoO 3 The RIR value of the β crystal of B and MoO 3 The integral intensity I of (2θ: around 23.01°, No. 86426 (Inorganic Crystal Structure Database, ICSD)) which belongs to the (011) plane of the β crystal of B Using the formula (2), MoO 3 The α crystal content (%) can be calculated. MoO 3 α crystal content (%) = (I A / K A ) / ((I A / K A )+(I B / K B ))×100 (2) Here, the RIR values can be those listed in the ICSD database, and the analysis can be performed using integrated powder X-ray analysis software (PDXL2, manufactured by Rigaku Corporation).
[0051] (Method of manufacturing molybdenum trioxide powder) The molybdenum trioxide powder may be produced by vaporizing a molybdenum oxide precursor compound to form molybdenum trioxide vapor and cooling the molybdenum trioxide vapor.
[0052] The method for producing the molybdenum trioxide powder includes calcining a raw material mixture containing a molybdenum oxide precursor compound and a metal compound other than the molybdenum oxide precursor compound, and vaporizing the molybdenum oxide precursor compound to form molybdenum trioxide vapor, and it is preferable that the proportion of the metal compound relative to 100 mass% of the raw material mixture is 70 mass% or less, calculated as the oxide.
[0053] The method for producing the molybdenum trioxide powder can be suitably carried out using a production apparatus 1 shown in FIG.
[0054] FIG. 1 is a schematic diagram of an example of an apparatus used for producing the molybdenum trioxide powder. The production apparatus 1 includes a calcination furnace 2 for calcining a molybdenum oxide precursor compound or the raw material mixture and vaporizing the molybdenum oxide precursor compound, a cross-shaped cooling pipe 3 connected to the calcination furnace 2 for powdering the molybdenum trioxide vapor vaporized by the calcination, and a recovery device 4 as a recovery means for recovering the molybdenum trioxide powder powdered in the cooling pipe 3. At this time, the calcination furnace 2 and the cooling pipe 3 are connected via an exhaust port 5. In addition, the cooling pipe 3 has an opening adjustment damper 6 at the left end of an outside air intake port (not shown) and an observation window 7 at the upper end. The recovery device 4 is connected to an exhaust device 8 as a first blowing means. The exhaust device 8 exhausts air, so that the recovery device 4 and the cooling pipe 3 are sucked, and outside air is blown into the cooling pipe 3 from the opening adjustment damper 6 of the cooling pipe 3. That is, the exhaust device 8 performs a suction function, and thus air is passively blown to the cooling pipe 3. The production apparatus 1 may have an external cooling device 9, which makes it possible to arbitrarily control the cooling conditions for the molybdenum trioxide vapor generated from the firing furnace 2.
[0055] By using the opening adjustment damper 6 to take in air from the outside air intake port and cool the molybdenum trioxide vapor vaporized in the sintering furnace 2 in an air atmosphere to produce molybdenum trioxide powder, the ratio (I / II) can be made greater than 1.1. In the molybdenum trioxide powder, MoO 3 When molybdenum trioxide vapor is cooled using liquid nitrogen or the like in a nitrogen atmosphere with a low oxygen concentration, the oxygen vacancy density increases and the ratio (I / II) tends to decrease.
[0056] The molybdenum oxide precursor compound is not particularly limited as long as it is a precursor compound for forming molybdenum trioxide powder consisting of an aggregate of primary particles containing the β crystal structure of molybdenum trioxide.
[0057] The molybdenum oxide precursor compound is not particularly limited as long as it can form molybdenum trioxide vapor by firing. Examples of the molybdenum oxide precursor compound include metallic molybdenum, molybdenum trioxide, molybdenum dioxide, molybdenum sulfide, ammonium molybdate, and phosphomolybdic acid (H 3 PMo 12 O 40 ), silicomolybdic acid (H 4 SiMo 12 O 40 ), aluminum molybdate, silicon molybdate, magnesium molybdate (MgMo n O 3n+1 (n=1-3)), sodium molybdate (Na 2 Mo n O 3n+1 (n=1-3)), titanium molybdate, iron molybdate, potassium molybdate (K 2 Mo n O 3n+1 (n=1-3)), zinc molybdate, boron molybdate, lithium molybdate (Li 2 Mo n O 3n+1 (n=1 to 3)), cobalt molybdate, nickel molybdate, manganese molybdate, chromium molybdate, cesium molybdate, barium molybdate, strontium molybdate, yttrium molybdate, zirconium molybdate, copper molybdate, etc. These molybdenum oxide precursor compounds may be used alone or in combination of two or more. The form of the molybdenum oxide precursor compound is not particularly limited, and may be, for example, a powder such as molybdenum trioxide, or a liquid such as an aqueous solution of ammonium molybdate. A powder form that is easy to handle and has good energy efficiency is preferable.
[0058] It is preferable to use commercially available α-crystalline molybdenum trioxide as the molybdenum oxide precursor compound. When ammonium molybdate is used as the molybdenum oxide precursor compound, it is converted to thermodynamically stable molybdenum trioxide by calcination, and the vaporized molybdenum oxide precursor compound becomes the molybdenum trioxide.
[0059] Among these molybdenum oxide precursor compounds, it is preferable to contain molybdenum trioxide from the viewpoint of facilitating control of the purity, average primary particle size, and crystal structure of the obtained molybdenum trioxide powder.
[0060] Molybdenum trioxide vapor can also be formed by calcining a raw material mixture containing a molybdenum oxide precursor compound and a metal compound other than the molybdenum oxide precursor compound.
[0061] The metal compound other than the molybdenum oxide precursor compound is not particularly limited, and examples thereof include aluminum compounds, silicon compounds, titanium compounds, magnesium compounds, sodium compounds, potassium compounds, zirconium compounds, yttrium compounds, zinc compounds, copper compounds, iron compounds, etc. Among these, it is preferable to use aluminum compounds, silicon compounds, titanium compounds, and magnesium compounds.
[0062] There are cases where an intermediate is generated between a molybdenum oxide precursor compound and a metal compound other than the molybdenum oxide precursor compound. Even in this case, the intermediate is decomposed by firing, and molybdenum trioxide can be vaporized in a thermodynamically stable form.
[0063] As the metal compound other than the molybdenum oxide precursor compound, it is preferable to use an aluminum compound among these in order to prevent damage to the firing furnace, and it is also possible not to use a metal compound other than the molybdenum oxide precursor compound in order to improve the purity of the molybdenum trioxide powder.
[0064] Examples of aluminum compounds include aluminum chloride, aluminum sulfate, basic aluminum acetate, aluminum hydroxide, boehmite, pseudo-boehmite, transition aluminum oxides (such as γ-aluminum oxide, δ-aluminum oxide, and θ-aluminum oxide), α-aluminum oxide, and mixed aluminum oxides having two or more crystal phases.
[0065] When a raw material mixture containing a molybdenum oxide precursor compound and a metal compound other than the molybdenum oxide precursor compound is fired, the content of the molybdenum oxide precursor compound relative to 100 mass% of the raw material mixture is preferably 40 to 100 mass%, may be 45 to 100 mass%, or may be 50 to 100 mass%.
[0066] The firing temperature varies depending on the molybdenum oxide precursor compound, metal compound, and desired molybdenum trioxide powder used, but is usually preferably a temperature at which the intermediate can be decomposed. For example, when a molybdenum compound is used as the molybdenum oxide precursor compound and an aluminum compound is used as the metal compound, aluminum molybdate may be formed as an intermediate, so the firing temperature is preferably 500 to 1500°C, more preferably 600 to 1550°C, and even more preferably 700 to 1600°C.
[0067] The firing time is not particularly limited, and can be, for example, 1 minute to 30 hours, 10 minutes to 25 hours, or 100 minutes to 20 hours.
[0068] The heating rate varies depending on the molybdenum oxide precursor compound and the metal compound used, and the properties of the desired molybdenum trioxide powder, but from the viewpoint of production efficiency, the heating rate is preferably 0.1° C. / min to 100° C. / min, more preferably 1° C. / min to 50° C. / min, and even more preferably 2° C. / min to 10° C. / min.
[0069] The internal pressure in the calcination furnace is not particularly limited and may be positive pressure or reduced pressure, but from the viewpoint of suitably discharging the molybdenum oxide precursor compound from the calcination furnace to a cooling pipe, it is preferable to carry out the calcination under reduced pressure. A specific degree of reduced pressure is preferably -5000 Pa to -10 Pa, more preferably -2000 Pa to -20 Pa, and even more preferably -1000 Pa to -50 Pa. A degree of reduced pressure of -5000 Pa or more is preferable because it does not require excessive airtightness or mechanical strength of the calcination furnace, and it is possible to reduce the manufacturing cost. On the other hand, a degree of reduced pressure of -10 Pa or less is preferable because it is possible to prevent clogging of the molybdenum oxide precursor compound at the exhaust port of the calcination furnace.
[0070] When gas is blown into the firing furnace during firing, the temperature of the gas blown is preferably 5 to 500°C, and more preferably 10 to 100°C.
[0071] The gas blowing speed is preferably 1 L / min to 500 L / min, and more preferably 10 L / min to 200 L / min, relative to the effective volume of the firing furnace of 100 L.
[0072] The temperature of the vaporized molybdenum trioxide vapor varies depending on the type of molybdenum oxide precursor compound used, but is preferably 200 to 2000° C., and more preferably 400 to 1500° C. When the temperature of the vaporized molybdenum trioxide vapor is 2000° C. or lower, it usually tends to be easily pulverized in a cooling pipe by blowing outside air (0 to 100° C.).
[0073] The discharge rate of molybdenum trioxide vapor discharged from the calcination furnace can be controlled by the amount of the molybdenum oxide precursor compound and the amount of the metal compound used, the temperature of the calcination furnace, the gas blown into the calcination furnace, and the diameter of the calcination furnace exhaust port. Although it varies depending on the cooling capacity of the cooling piping, the discharge rate of molybdenum trioxide vapor from the calcination furnace to the cooling piping is preferably 0.001 g / min or more and 100 g / min or less, and more preferably 0.1 g / min or more and 50 g / min or less.
[0074] The content of molybdenum trioxide vapor contained in the gas discharged from the calciner is preferably 0.01 g / min to 1000 mg / L, more preferably 1 g / min to 500 mg / Lg / min.
[0075] The molybdenum trioxide vapor is then cooled and pulverized. The molybdenum trioxide vapor is cooled by lowering the temperature of the cooling pipe. In this case, the cooling means may be, as described above, cooling by blowing gas into the cooling pipe, cooling by a cooling mechanism of the cooling pipe, or cooling by an external cooling device.
[0076] The molybdenum trioxide vapor is preferably cooled in an air atmosphere. By cooling the molybdenum trioxide vapor in an air atmosphere to obtain molybdenum trioxide powder, the ratio (I / II) can be made larger than 1.1, and in the molybdenum trioxide powder, MoO 3 The β crystal structure is easily obtained.
[0077] The cooling temperature (temperature of the cooling pipe) is not particularly limited, but is preferably from -100 to 600°C, and more preferably from -50 to 400°C.
[0078] The cooling rate of the molybdenum trioxide vapor is not particularly limited, but is preferably from 100° C. / s to 100,000° C. / s, and more preferably from 1,000° C. / s to 50,000° C. / s. The faster the cooling rate of the molybdenum trioxide vapor, the smaller the particle size and the larger the specific surface area of the molybdenum trioxide powder that is obtained tends to be.
[0079] When the cooling means is a means for cooling by blowing gas into a cooling pipe, the temperature of the blown gas is preferably -100 to 300°C, and more preferably -50 to 100°C.
[0080] The gas flow rate is 0.1 m 3 / min or more 20m 3 / min or less is preferable, and 3 / min or more 10m 3 It is more preferable that the gas blowing speed is 0.1 m / min or less. 3 / min or more, a high cooling rate can be realized and clogging of the cooling pipes can be prevented, which is preferable. 3 / min or less is preferable because it eliminates the need for expensive first blowing means (exhaust fan, etc.), thereby enabling the manufacturing cost to be reduced.
[0081] The powder obtained by cooling the molybdenum trioxide vapor is transported to a recovery machine and recovered.
[0082] The method for producing the molybdenum trioxide powder may further comprise calcining the powder obtained by cooling the molybdenum trioxide vapor again at a temperature of 100 to 320°C.
[0083] That is, the molybdenum trioxide powder obtained by the method for producing molybdenum trioxide powder may be fired again at a temperature of 100 to 320°C. The firing temperature of the second firing may be 120 to 280°C, or 140 to 240°C. The firing time of the second firing may be, for example, 1 min to 4 h, 10 min to 5 h, or 100 min to 6 h. However, by firing again, a part of the β crystal structure of molybdenum trioxide disappears, and when fired at a temperature of 350°C or higher for 4 hours, the β crystal structure in the molybdenum trioxide powder disappears, the ratio (β(011) / α(021)) becomes 0, and the reactivity with carbon is impaired.
[0084] According to the method for producing molybdenum carbide of the present embodiment, it is possible to obtain molybdenum carbide having a desired particle structure and composition, and the method for producing molybdenum carbide of the present embodiment has the advantages of being mass-produced, not requiring dangerous high-pressure equipment, and not requiring a post-treatment process.
[0085] <First catalyst ink> The catalyst ink according to this embodiment (hereinafter also referred to as the "first catalyst ink") contains the molybdenum carbide according to the above embodiment and a solvent. The solvent is not particularly limited, but examples thereof include alcohol solvents such as methanol and ethanol, and mixed solvents of alcohol solvents and water. Among these, methanol and ethanol are preferred as the solvent. In the present embodiment, the solvent may be one type only, or two or more types.
[0086] The first catalyst ink of this embodiment may further contain a conductive material. Examples of the conductive material include carbon and metals, which have high conductivity. The first catalyst ink may contain only one type of conductive material, or may contain two or more types of conductive materials.
[0087] Examples of the conductive material include carbon black such as acetylene black, Cabot carbon black, and Ketjen black, graphite, carbon fiber, metal powder, etc. Ketjen black has a high specific surface area and electrical conductivity, and is also excellent in that it can suppress the aggregation of molybdenum carbide.
[0088] Examples of the metal that is the conductive material include gold, silver, copper, palladium, aluminum, rhodium, molybdenum, tungsten, iron, nickel, cobalt, and indium.
[0089] The first catalyst ink according to this embodiment may contain only one type of metal as a conductive material, or may contain two or more types of metal.
[0090] The first catalyst ink according to this embodiment may, for example, contain no metal but contain carbon as a conductive material, may contain no carbon but contain a metal, or may contain both a metal and carbon.
[0091] The first catalyst ink according to this embodiment can be applied to, for example, a working electrode substrate to form a catalyst layer.
[0092] The first catalyst ink according to this embodiment may further contain a polymer electrolyte. The polymer electrolyte may be one generally used in the formation of a catalyst layer.Specific examples of the polymer electrolyte include perfluorocarbon polymers having sulfonic acid groups (e.g., Nafion (registered trademark)), hydrocarbon polymer compounds having sulfonic acid groups, polymer compounds doped with inorganic acids such as phosphoric acid, organic / inorganic hybrid polymers partially substituted with proton-conductive functional groups, and proton conductors in which a polymer matrix is impregnated with a phosphoric acid solution or a sulfuric acid solution.
[0093] <Composite of precious metal particles and molybdenum carbide> The composite according to this embodiment (hereinafter also referred to as the "first composite") is a composite of noble metal particles having an average particle size of 20 nm or less and the molybdenum carbide according to the above embodiment.
[0094] (Precious metal particles) In this embodiment, the noble metal particles are not particularly limited, but are preferably gold, silver, platinum, palladium, rhodium, or iridium, and more preferably palladium. In this embodiment, the noble metal particles may be of only one type, or of two or more types.
[0095] When the precious metal is palladium, the palladium particles contained in the first composite of the embodiment are granular structures containing palladium, and are composited with the molybdenum carbide particles to form a composite of palladium and molybdenum carbide.
[0096] The shape of the palladium particles is not particularly limited, and examples of the shape include spherical and semi-spherical shapes.
[0097] The form in which the palladium particles are contained in the first composite according to the embodiment is not particularly limited, but the palladium particles may be present on the surfaces of the molybdenum carbide particles, or may be adhered to the surfaces of the molybdenum carbide particles.
[0098] The number of palladium particles present per 100 nm×100 nm surface area of the surface of the molybdenum carbide particle may be, for example, 5 to 5,000 particles, or 10 to 1,000 particles.
[0099] The average particle size of the palladium particles is 20 nm or less, optionally 15 nm or less, or optionally 10 nm or less.
[0100] The lower limit of the average particle size of the palladium particles may be, for example, 0.5 nm or more, 0.7 nm or more, or 1 nm or more. An example of the range of the average particle size of the palladium particles may be 0.5 nm or more and 20 nm or less, 0.7 nm or more and 15 nm or less, or 1 nm or more and 10 nm or less.
[0101] The average particle size of the palladium particles is determined by photographing the first composite of this embodiment with a transmission electron microscope (TEM) and examining the palladium particles observed in the two-dimensional image, measuring the maximum distance between two points on the contour line of 50 randomly selected palladium particles, and then using the average value.
[0102] Palladium particles are aggregates of palladium (Pd) atoms and contain palladium. The form of palladium contained in the composite of the embodiment is not particularly limited, and may be contained in the palladium particles as a palladium compound, for example.
[0103] In this embodiment, the diffraction pattern of the palladium particles in XRD analysis preferably does not show the crystal structure of palladium metal crystals, in which case the first composite according to this embodiment exhibits excellent catalytic performance.
[0104] In this embodiment, the palladium particles may include amorphous palladium. The palladium particles may include palladium that is not in a form in which a portion of the molybdenum in the crystal structure of molybdenum disulfide is substituted. The palladium particles may include palladium with a valence of zero. The palladium particles may include palladium that does not have the crystal structure of palladium metal crystals.
[0105] Regarding the content ratio of palladium in the above-mentioned form, the palladium particles may contain 50% or more of amorphous palladium on a molar basis relative to the palladium contained in the palladium particles. The palladium particles may contain 50% or more of palladium that is not in a form substituted with a part of molybdenum in the crystal structure of molybdenum disulfide on a molar basis relative to the palladium contained in the palladium particles. The palladium particles may contain 50% or more of zero-valent palladium on a molar basis relative to the palladium contained in the palladium particles. The palladium particles may contain 50% or more of palladium that does not have a crystal structure (close-packed structure) of palladium metal crystals on a molar basis relative to the palladium contained in the palladium particles.
[0106] The first complex of the present embodiment may include amorphous palladium. The first complex of the present embodiment may include palladium that is not in a form substituted with a portion of the molybdenum in the crystal structure of molybdenum carbide. The first complex of the present embodiment may include palladium with a valence of 0. The first complex of the present embodiment may include palladium that does not have the crystal structure of palladium metal crystal.
[0107] Regarding the content of palladium in the above embodiment, the first composite of the embodiment may contain 50% or more of amorphous palladium on a molar basis relative to the palladium contained in the first composite. The first composite of the embodiment may contain palladium that is not in a form substituted with a part of the molybdenum in the crystal structure of molybdenum carbide on a molar basis relative to the palladium contained in the first composite. The first composite of the embodiment may contain 50% or more of palladium with a valence of zero on a molar basis relative to the palladium contained in the composite. The first composite of the embodiment may contain 50% or more of palladium that does not have a crystal structure of palladium metal crystal on a molar basis relative to the palladium contained in the first composite.
[0108] The palladium in the first composite of the embodiment may form palladium clusters. Also, the palladium in the palladium particles may form palladium clusters.
[0109] The presence of a crystal structure containing palladium can be detected from a diffraction profile obtained by XRD analysis of the first complex of the embodiment as a sample.
[0110] According to the first composite of the embodiment described above, the molybdenum carbide and metal particles (preferably palladium particles) are composited together, and thus excellent catalytic performance can be exhibited. Furthermore, it is believed that when the precious metal in the precious metal particles does not form a crystal structure of precious metal crystals, but is present in the molybdenum carbide preferably as an aggregate of precious metal atoms, it is possible to exhibit even more excellent catalytic performance.
[0111] The first composite of the embodiment can be used as a catalyst, and in particular can be suitably used as a hydrogen generation catalyst applied to water electrolysis and the like. Moreover, the first composite of the embodiment can be suitably used as an electrode material used as a constituent material of an electrode catalyst layer.
[0112] <Method for producing the first composite> The manufacturing method of the first composite of the embodiment is not particularly limited, but typically includes a step of mixing the molybdenum carbide with a precious metal solution, and more preferably includes a step of mixing the molybdenum carbide with a palladium solution. In this embodiment, the noble metal solution may be of only one type, or of two or more types.
[0113] The palladium solution can be obtained by dissolving any palladium source in a solvent. The palladium source may be any palladium compound capable of producing a palladium solution, such as palladium acetate, palladium nitrate, palladium nitrite, palladium sulfate, palladium carbonate, palladium chloride, palladium hydroxide, palladium oxide, etc. In this embodiment, the palladium solution may be of only one type, or of two or more types.
[0114] The solvent may be any solvent capable of dissolving the palladium source, and examples of the solvent include alcohols such as methanol, benzene, dichloromethane, acetone, and chloroform. In the present embodiment, the solvent may be one type only, or two or more types.
[0115] The method of mixing is not particularly limited, but it is preferable to mix a palladium solution with a dispersion of molybdenum carbide.
[0116] The dispersion of molybdenum carbide can be obtained by mixing the solvent exemplified for the above palladium solution with molybdenum carbide.
[0117] A composite of molybdenum carbide and palladium particles can be formed by mixing a palladium solution with molybdenum carbide to obtain a mixture and then contacting the molybdenum carbide with the palladium solution.
[0118] From the viewpoint of preventing aggregation of molybdenum carbide, for example, it is preferable to stir the mixture of the palladium solution and the molybdenum carbide, with the stirring speed being, for example, 50 to 1000 rpm.
[0119] The concentration of palladium in the palladium solution may be, for example, 0.00001 to 0.1 mol / L, or 0.0001 to 0.01 mol / L.
[0120] The temperature of the mixture of molybdenum carbide and palladium solution may be at a level that allows the formation of the first composite, and may be, for example, 10 to 100°C, or 20 to 80°C.
[0121] The retention time of the mixture of molybdenum carbide and palladium solution may be long enough to form the first composite, and may be, for example, from 10 minutes to 48 hours, or from 30 minutes to 12 hours.
[0122] In the first embodiment of the method for producing a composite, the mixture of molybdenum carbide and palladium solution may be irradiated with light in order to promote the photoreduction of palladium. The light irradiation may be performed by appropriately selecting the amount of light and wavelength to an extent that the photoreduction of palladium occurs. The light irradiation may be performed by installing a light source to control the light intensity, or may be performed by irradiating with light in a normal indoor environment (from fluorescent lamps, LEDs, or the like) or natural light.
[0123] In the method for producing the first composite of the embodiment, the first composite can be produced without performing a heat treatment. For example, the obtained first composite or a mixture of the palladium solution and the molybdenum carbide is preferably not heated to 200°C or higher, more preferably not heated to above 100°C, and even more preferably not heated to above 80°C.
[0124] After the complex is formed from the mixture, the complex is separated by a process such as centrifugation or drying, and the first complex of the embodiment can be easily recovered.
[0125] <Hydrogen generation catalyst> The first composite according to the embodiment can be suitably used as a catalyst in the hydrogen generation reaction (HER) (sometimes referred to as "hydrogen generation catalyst" in this specification). The first composite according to the embodiment can also be used as a hydrogen generation catalyst when used in combination with a conductive material. That is, a preferred hydrogen generation catalyst includes, for example, one containing the first composite according to the embodiment, and the hydrogen generation catalyst may further contain a conductive material in addition to the first composite according to the embodiment. The catalytic activity of the hydrogen generation catalyst containing the first composite according to the embodiment and a conductive material in the hydrogen generation reaction (HER) is further increased.
[0126] The conductive material may be any known material. Examples of the conductive material include carbon and metals, which have high conductivity. The hydrogen generation catalyst may contain only one type of conductive material, or may contain two or more types of conductive materials.
[0127] Examples of the conductive material include carbon black such as acetylene black, Cabot carbon black, and Ketjen black, graphite, carbon fiber, metal powder, etc. Ketjen black has a high specific surface area and electrical conductivity, and is also excellent in that it can suppress the aggregation of molybdenum carbide.
[0128] Examples of the metal that is the conductive material include gold, silver, copper, aluminum, rhodium, molybdenum, tungsten, iron, nickel, cobalt, and indium. The metal as the conductive material is different from the noble metal of the first complex of the embodiment, and in the hydrogen generation catalyst, it is merely mixed with the first complex of the embodiment.
[0129] The hydrogen generation catalyst may contain only one type of metal as a conductive material, or may contain two or more types of metal.
[0130] The hydrogen generation catalyst may, for example, contain no metal but contain carbon as a conductive material, may contain no carbon but contain a metal, or may contain both a metal and carbon.
[0131] In the hydrogen generation catalyst, the content of the conductive material is preferably 0.1 to 50 mass %, and more preferably 0.5 to 40 mass %, relative to the content of the first composite of the embodiment.
[0132] In the hydrogen generation catalyst, the ratio of the total content of the first composite of the embodiment and the conductive material to the total mass (100 mass%) of the hydrogen generation catalyst is preferably 80 mass% or more, more preferably 90 mass% or more, and even more preferably 95 mass% or more, and may be, for example, any of 97 mass% or more and 99 mass% or more, or may be 100 mass%. When the ratio is equal to or more than the lower limit, the catalytic activity of the hydrogen generation catalyst in the hydrogen generation reaction (HER) becomes higher. The ratio may be 100 mass% or less.
[0133] <Second catalyst ink> The first composite is suitable as a component of a catalyst ink. The catalyst ink of the embodiment (hereinafter also referred to as "second catalyst ink") contains the first complex of the embodiment and a solvent. The second catalyst ink of the embodiment may contain the first complex of the embodiment, a polymer electrolyte, and a solvent.
[0134] The second catalyst ink of this embodiment may further contain a conductive material, such as those exemplified above.
[0135] The second catalyst ink can be applied, for example, to a working electrode substrate to form a catalyst layer.
[0136] The polymer electrolyte may be one generally used in catalyst layers.Specific examples include perfluorocarbon polymers having sulfonic acid groups (e.g., Nafion (registered trademark)), hydrocarbon polymer compounds having sulfonic acid groups, polymer compounds doped with inorganic acids such as phosphoric acid, organic / inorganic hybrid polymers partially substituted with proton-conductive functional groups, and proton conductors in which a polymer matrix is impregnated with a phosphoric acid solution or a sulfuric acid solution.
[0137] The solvent may be one in which the first composite of the embodiment can be dispersed and which can be applied to a working electrode substrate to form a catalyst layer. The solvent preferably contains an alcohol such as 1-propanol, 2-propanol, 1-butanol, 2-butanol, 1-pentanol, 2-pentanol, 1-hexanol, 2-hexanol, 1-heptanol, or 2-heptanol.
[0138] <Composites of transition metal species and molybdenum carbide> The composite according to this embodiment (hereinafter also referred to as the "second composite") is a composite of at least one transition metal species selected from the group consisting of transition metals and transition metal compounds, and the molybdenum carbide.
[0139] (Transition metals, transition metal compounds) In this embodiment, the transition metal is not particularly limited, but nickel, iron, cobalt, chromium, vanadium, manganese, copper, zinc, ruthenium, and iridium are preferable, and nickel, iron, cobalt, and manganese are more preferable. In the present embodiment, the transition metal compound is not particularly limited, and examples thereof include hydroxides of transition metals and oxides of transition metals. Among them, nickel compounds are preferred as the transition metal compound, and Ni(OH) 2 The transition metal compound may be a compound containing two or more transition metals, for example, NiFeO x etc. In this embodiment, the transition metal species may be only one type, or may be two or more types.
[0140] The shape of the primary particles of the nickel compound in a two-dimensional image taken by a transmission electron microscope (TEM) may be particulate, spherical, plate-like (sheet-like), needle-like, string-like, or ribbon-like, or may include a combination of these shapes, as observed by visual observation or in a photograph. In this embodiment, the shape of the primary particles of the nickel compound in a two-dimensional image taken by a TEM is preferably sheet-like.
[0141] According to the second composite of the embodiment, the molybdenum carbide and a transition metal species (preferably a nickel compound) are composited together, and thus excellent catalytic performance can be exhibited.
[0142] The second composite of the embodiment can be used as a catalyst, and in particular can be suitably used as an oxygen generating catalyst applied to water electrolysis and the like. Moreover, the second composite of the embodiment can be suitably used as an electrode material used as a constituent material of an electrode catalyst layer.
[0143] <Method for producing the second composite> The method for producing the second composite of the embodiment is not particularly limited, but typically includes a step of mixing the molybdenum carbide with a solution of a transition metal source.
[0144] Examples of the transition metal source include acetates of transition metals, nitrates of transition metals, nitrites of transition metals, sulfates of transition metals, carbonates of transition metals, chlorides of transition metals, hydroxides of transition metals, and oxides of transition metals. Of these, nickel acetate is preferred as the transition metal source. The transition metal source is preferably an aqueous solution, and more preferably an aqueous nickel acetate solution. In this embodiment, the transition metal source may be of only one type, or of two or more types.
[0145] When using an aqueous solution of nickel acetate as a transition metal source, an amine is generated in the aqueous solution of nickel acetate to provide a basic environment and produce the desired Ni(OH) 2 Urea may be added to facilitate the formation of
[0146] The above mixing method is not particularly limited, but it is preferable to mix a nickel solution with a dispersion of molybdenum carbide.
[0147] An example of the dispersion of molybdenum carbide is a mixture of water and molybdenum carbide.
[0148] A composite of molybdenum carbide and a nickel compound can be formed by mixing a nickel compound solution with molybdenum carbide to obtain a mixture and then contacting the molybdenum carbide with the nickel compound solution.
[0149] From the viewpoint of preventing aggregation of molybdenum carbide, for example, it is preferable to stir the mixture of the nickel compound solution and the molybdenum carbide, for example, at a speed of 50 to 1000 rpm.
[0150] The concentration of nickel in the nickel compound solution may be 0.0001 to 1 mol / L, or may be 0.001 to 0.1 mol / L.
[0151] The temperature of the mixture may be any temperature that allows the second complex to be formed, and may be, for example, 10 to 100°C, or 20 to 90°C.
[0152] The retention time of the mixture may be any length of time that allows the formation of a second complex, and may be, for example, from 10 minutes to 48 hours, or from 30 minutes to 12 hours.
[0153] In the method for producing the second composite of the embodiment, the second composite can be produced without performing a heat treatment. For example, the obtained second composite or the mixture of the nickel compound solution and the molybdenum carbide is preferably not heated to 200°C or higher, more preferably not heated to above 100°C, and even more preferably not heated to above 80°C.
[0154] After the second complex is formed from the above mixture, the second complex can be separated by a process such as centrifugation or drying, and the second complex of the embodiment can be easily recovered.
[0155] <Oxygen generation catalyst> The second composite of the embodiment can be suitably used as a catalyst in the oxygen generating reaction (OER) (sometimes referred to as "oxygen generating catalyst" in this specification). The second composite of the embodiment can also be used as an oxygen generating catalyst when used in combination with a conductive material. That is, a preferred oxygen generating catalyst is, for example, one that contains the second composite of the embodiment, and the oxygen generating catalyst may further contain a conductive material in addition to the second composite of the embodiment. The catalytic activity of the oxygen generating catalyst in the oxygen generating reaction (OER) that contains the second composite of the embodiment and a conductive material is further increased.
[0156] The conductive material may be the same as the conductive material in the oxygen generating catalyst.
[0157] The oxygen generating catalyst may contain only one type of metal as a conductive material, or may contain two or more types of metal.
[0158] The oxygen generating catalyst may, for example, contain no metal but contain carbon as a conductive material, may contain no carbon but contain a metal, or may contain both a metal and carbon.
[0159] In the oxygen generating catalyst, the content of the conductive material is preferably 0.1 to 50 mass %, and more preferably 0.5 to 40 mass %, relative to the content of the second composite of the embodiment.
[0160] In the oxygen generating catalyst, the ratio of the total content of the second composite of the embodiment and the conductive material to the total mass (100 mass%) of the oxygen generating catalyst is preferably 80 mass% or more, more preferably 90 mass% or more, and even more preferably 95 mass% or more. For example, it may be any of 97 mass% or more and 99 mass% or more, or it may be 100 mass%. When the ratio is equal to or more than the lower limit, the catalytic activity of the oxygen generating catalyst in the oxygen generating reaction (OER) becomes higher. The ratio may be equal to or less than 100 mass%.
[0161] When the oxygen generating catalyst of the embodiment is applied to a battery, the electrolyte is not particularly limited and any known electrolyte can be used, but a potassium hydroxide solution is preferred.
[0162] <The third catalyst ink> The second composite is suitable as a component of a catalyst ink. The catalyst ink of the embodiment (hereinafter also referred to as "third catalyst ink") contains the second complex of the embodiment and a solvent. The third catalyst ink of the embodiment may contain the second complex of the embodiment, a polymer electrolyte, and a solvent.
[0163] The third catalyst ink of this embodiment may further contain a conductive material, such as those exemplified above.
[0164] The third catalyst ink can be applied, for example, to a working electrode substrate to form a catalyst layer.
[0165] The polymer electrolyte and the solvent may be the same as those used in the second catalyst ink. EXAMPLES
[0166] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0167] (Manufacturing of molybdenum trioxide powder) Molybdenum trioxide was produced using an RHK simulator (manufactured by Noritake Co., Ltd.) as the firing furnace and a VF-5N dust collector (manufactured by Amano Corporation) as the dust collector. 1.5 kg of aluminum hydroxide (manufactured by Nippon Light Metals Co., Ltd.) and 1 kg of molybdenum trioxide (manufactured by Nippon Muki Co., Ltd.) were mixed, then charged into a sagger and fired at a temperature of 1100°C for 10 hours. During firing, outside air (air flow rate: 150 L / min, outside air temperature: 25°C) was introduced from the side and bottom of the firing furnace. After evaporating in the furnace, molybdenum trioxide was cooled near the dust collector and precipitated as particles, and 900 g of molybdenum trioxide 1 was obtained by the dust collector.
[0168] The median diameter D50 of the primary particles determined by dynamic light scattering is 87.8 nm, and the purity of molybdenum trioxide 1 (MoO 3 It was confirmed that the content of 99.9% by mass. In addition, when the crystal structure of molybdenum trioxide (1) was analyzed by X-ray diffraction (XRD), peaks attributable to α-crystalline molybdenum trioxide and β-crystalline molybdenum trioxide were observed, but no other peaks were observed. Next, the peak intensity ratios of the (011) plane of the β-crystalline and the (021) plane of the α-crystalline were compared, and the β(011) / α(021) ratio was found to be 4. Furthermore, the integrated powder X-ray analysis software PDXL2 manufactured by Rigaku Corporation was applied, and the XRD instrument constant was determined using LaB6 (NIST SRM660c LaB6 Standard Powder) as the standard substance. The crystallite size was evaluated using the Scherrer method, and it was confirmed that molybdenum trioxide (1) has a crystal structure including α-crystalline with an average crystallite size of 15.7 nm and β-crystalline with an average crystallite size of 16.8 nm.
[0169] <Evaluation of Molybdenum Oxide Powder> [Method for measuring the average particle size of primary particles of molybdenum trioxide powder] 0.1g of molybdenum trioxide powder was added to 10cc of ethanol, and ultrasonic treatment was performed in an ice bath for 4 hours. The concentration was then adjusted appropriately with ethanol to a range measurable by a dynamic light scattering particle size distribution measuring device (MicrotracBEL Nanotrac WaveII) to obtain a measurement sample. Using this measurement sample, the particle size distribution in the particle size range of 0.0001 to 10μm was measured by a dynamic light scattering particle size distribution measuring device (MicrotracBEL Nanotrac WaveII) and the median diameter D50 was calculated. However, for those with a median diameter D50 exceeding 10μm, the solution was similarly prepared and the particle size distribution in the particle size range of 0.015 to 500μm was measured by a laser diffraction particle size distribution measuring device (Shimadzu SALD-7000) to calculate the median diameter D50.
[0170] [Crystal structure analysis of molybdenum trioxide powder: XRD method] A sample of the molybdenum compound obtained in each Example was loaded into a measurement sample holder with a depth of 0.5 mm, which was then set in an X-ray diffraction (XRD) device (Ultima IV manufactured by Rigaku Corporation, using a parallel beam optical system with a scintillation counter detector and a rotating stage), and measurement was performed under the conditions of Cu / Kα radiation, 40 kV / 40 mA, scan speed (2θ) 2° / min, step (2θ) 0.02°, and scan range (2θ) 10° to 70°.
[0171] [Method for measuring crystallite size of molybdenum trioxide powder] The integrated powder X-ray diffraction software PDXL2 manufactured by Rigaku Corporation was used, and the XRD instrument constants were determined using LaB6 (NIST SRM660c LaB6 Standard Powder) as a standard substance, and the crystallite size was evaluated using the Scherrer method (Scherrer constant K = 0.94 was used).
[0172] [Purity measurement of molybdenum trioxide: XRF analysis] Using a Primus IV X-ray fluorescence analyzer (Rigaku Corporation), about 20-30 mg of the collected molybdenum trioxide powder sample was placed on filter paper, covered with PP film, and subjected to composition analysis. The amount of molybdenum determined from the XRF analysis results was calculated as molybdenum trioxide equivalent (mass%) relative to 100 mass% of the molybdenum trioxide powder.
[0173] (Example 1: Mo 2 Synthesis of C) 0.5 g of molybdenum trioxide 1, 0.17 g of Ketjen black (EC300J manufactured by Lion Specialty Chemicals Co., Ltd.), 0.33 g of sodium chloride, and 0.33 g of potassium chloride were mixed in a mortar for 1 minute, then charged into a crucible and fired at 850°C for 3 hours in a nitrogen atmosphere. After natural cooling, the fired product was washed with ion-exchanged water to remove salts. According to XRD measurement, the obtained molybdenum carbide was molybdenum carbide (Mo 2 C) α crystal structure.
[0174] (Examples 2 to 3: Mo 2 Synthesis of C) Molybdenum carbide was synthesized in the same manner as in Example 1, except that the raw materials were changed as shown in Table 1.
[0175] Comparative Example 1 Commercially available molybdenum carbide (manufactured by Kojundo Chemical Laboratory Co., Ltd.) was evaluated in the same manner as the molybdenum carbides of Examples 1 to 3. The results are shown in Table 2.
[0176] Comparative Example 2 Ketjen black (EC300J manufactured by Lion Specialty Chemicals Co., Ltd.) was evaluated in the same manner as the molybdenum carbides of Examples 1 to 3. The results are shown in Table 2.
[0177] Comparative Example 3 203.9 g of Ketjen black (EC300J manufactured by Lion Specialty Chemicals Co., Ltd.) and 33.6 g of molybdenum carbide (manufactured by Kojundo Chemical Laboratory Co., Ltd.) were mixed in a mortar. The resulting mixture was evaluated in the same manner as the molybdenum carbides of Examples 1 to 3. The results are shown in Table 2.
[0178] [Table 1]
[0179] In Table 1, "MoO 3 (1)" stands for molybdenum trioxide 1, and "KB" stands for Ketjen Black (EC300J manufactured by Lion Specialty Chemicals Co., Ltd.).
[0180] <Evaluation> The molybdenum carbides of Examples 1 to 3, the commercially available molybdenum carbide of Comparative Example 1, Ketjen Black of Comparative Example 2, and the mixture of Comparative Example 3 were evaluated as follows.
[0181] [Elemental analysis] The molybdenum content was determined by heated sealed acid decomposition-ICP-AES (inductively coupled plasma atomic emission spectrometry). More specifically, the sample was dissolved in a mixture of sulfuric acid and nitric acid at 180°C for 12 hours or more, and the measurement was performed under the following conditions. Inductively Coupled Plasma (ICP) emission spectrometry (instrument: Thermo Fisher Scientific iCAP 6300 DUO) PF power: 1150W Flow rate: 52rpm Auxiliary gas: 0.5L / min Nebulizer gas: 0.6L / min Plasma View: Axial The carbon content was determined by CHN elemental analysis (J Science Lab, MICROCORDER JM10).
[0182] [Specific surface area measurement: BET method] The molybdenum carbide samples were measured using a specific surface area meter (Microtrack Bell, BELSORP-mini), and the surface area per 1 g of sample measured from the amount of nitrogen gas adsorbed by the BET method was defined as the specific surface area (m 2 The results were calculated as the BET specific surface area (m 2 The results are shown in Table 2 as "(g)".
[0183] [Crystal structure analysis: XRD method] The molybdenum carbide samples obtained in each Example were filled into a measurement sample holder with a depth of 0.5 mm, which was then set in an X-ray diffraction (XRD) device (Ultima IV, manufactured by Rigaku Corporation) and measurements were performed under the conditions of Cu / Kα radiation, 40 kV / 40 mA, scan speed (2θ) 2° / min, and scan range (2θ) 10° to 70°. The results are shown in Table 2 as "crystallite size (nm)".
[0184] [Median diameter D 50 Measurement method] 0.1 g of sample powder was added to 20 cc of acetone, and ultrasonicated in an ice bath for 4 hours. The concentration was then adjusted with acetone to a suitable range within the measurable range of a dynamic light scattering particle size distribution analyzer (Microtrack Bell, Nanotrac WaveII) to obtain a measurement sample. Using this measurement sample, the particle size distribution in the particle size range of 0.0001 μm to 10 μm was measured with the dynamic light scattering particle size distribution analyzer, and the median diameter D, which is the particle diameter at which the volume cumulative percentage is 50%, was obtained. 50 was calculated. The result is "D 50 The values are shown in Table 2 as "(nm)".
[0185] [Analysis by Raman spectroscopy] The powder sample was placed on a slide glass and measured using a laser Raman spectrophotometer (JASCO Corporation, NRS-5500) under the following measurement conditions: excitation laser 532 nm, laser intensity 0.6 mW, exposure time 30 sec, and point measurement with an objective lens of 100x. After the measurement, the baseline-corrected XPS spectrum was analyzed using the analysis software Spectra manager. The results are shown in Table 2 as "G / D (au)".
[0186] [Method of measuring body fluid resistivity] Approximately 0.5 g of sample powder was placed in a measuring fixture, and the resistance was measured under a load of 4 to 20 kN using an automatic powder resistivity measuring system (MCP-PD600, manufactured by Nitto Seiko Air Analytec), and the volume resistivity was calculated from the volume of the powder. The results are shown in Table 2 as "Volume resistivity @ 64 MPa".
[0187] The results of the above measurements are shown in Table 2.
[0188] [Table 2]
[0189] The results of the XRD analysis are shown in Figure 2. As shown in Figure 2, all of the molybdenum carbides obtained in Examples 1 to 3 were molybdenum carbide (Mo 2 It was confirmed that the molybdenum carbides of Examples 1 to 3 all exhibited a crystal structure of molybdenum carbide (Mo 2 C) The crystal structure was confirmed to be α crystal.
[0190] Fig. 3 shows images obtained by a transmission electron microscope (TEM, manufactured by JEOL Ltd., JEM-1400) of the particles of Examples 1 to 3. As shown in Fig. 3, it was confirmed that all of the molybdenum carbides of Examples 1 to 3 had a sheet structure.
[0191] FIG. 4 shows an observation image of the particles of Example 1 obtained by a high-resolution transmission electron microscope (HRTEM, manufactured by JEOL Ltd., JEM-ARM300F). From the EDS mapping image, Mo and C are seen to overlap, and from the high-resolution TEM, Mo 2 From the crystal lattice image of C, the compound of Example 1 is Mo 2 It was confirmed that C was the main phase. In addition, an oxide layer (MoO 3 ) was recognized.
[0192] [Preparation of catalytic ink and evaluation of hydrogen evolution activity (1)] Ink was prepared by ultrasonic dispersion of 4 mg of any one of the molybdenum carbides of Examples 1 to 3, the commercially available molybdenum carbide of Comparative Example 1, the Ketjen Black of Comparative Example 2, and the mixture of Comparative Example 3, 2 mg of Ketjen Black, and 40 ul of 5% Nafion dispersion (Fujifilm Wako Pure Chemical Corporation Nafion dispersion solution) in 1 ml of ethanol for 1 hour. 20 ul of the obtained ink dispersion was applied to the electrode surface, and the surface liquid was naturally dried, and then the electrode was transferred to a vacuum dryer and dried at 60°C for 6 hours or more. The hydrogen generation activity of the prepared electrode was evaluated by a three-electrode method. The evaluation conditions were an LSV method, with a scan voltage range of -0.3V to 0V and a scan speed of 5mV / S. Current density 10mA / cm 2 Overpotential (mV) at 0.3V, current density (mA / cm 2 ) are shown in Table 3.
[0193] [Table 3]
[0194] (Example 4: Synthesis of palladium-molybdenum carbide composite 1) Example 1 100 mg of molybdenum carbide was dissolved in methanol (Kanto Chemical Co., Ltd., reagent, CH 3 The mixture was ultrasonically dispersed in 50 ml of palladium acetate (Kanto Chemical Co., Ltd., Pd(CH 3 COO) 2 After dissolving 42.2 mg of palladium in methanol, the resulting solution was added to the dispersion with stirring. The mixture was then stirred at room temperature for more than 2 hours under light irradiation. The precipitate in the dispersion was collected using a centrifuge, ultrasonically washed three times with water, and dried in a vacuum to obtain a Pd-modified molybdenum carbide powder (palladium-molybdenum carbide composite 1).
[0195] (Examples 5 to 6: Synthesis of palladium-molybdenum carbide composite 2 and palladium-molybdenum carbide composite 3) Palladium-molybdenum carbide composite 2 and palladium-molybdenum carbide composite 3 were synthesized in the same manner as in Example 4, except that the raw materials were changed as shown in Table 4.
[0196] ( Comparative Example 4 ) Commercially available molybdenum carbide (manufactured by Kojundo Chemical Laboratory Co., Ltd.) was evaluated in the same manner as for palladium-molybdenum carbide composites 1 to 3 in Examples 4 to 6. The results are shown in Table 5.
[0197] ( Comparative Example 5 ) Palladium-modified Ketjen Black (4% Pd-KB) was synthesized in the same manner as in Example 4, except that the raw materials were changed to those shown in Table 4.
[0198] [Table 4]
[0199] In Table 4, "Mo 2 "C-4" indicates the molybdenum carbide of Example 1, and "Mo 2 "C-6" indicates the molybdenum carbide of Example 2, and "KB" indicates Ketjen Black (EC300J manufactured by Lion Specialty Chemicals Co., Ltd.).
[0200] <Evaluation> Palladium-molybdenum carbide composites 1 to 3 of Examples 4 to 6, commercially available molybdenum carbide of Comparative Example 4, and 4% Pd-KB of Comparative Example 5 were evaluated as follows.
[0201] [XRF analysis] Using a Primus IV X-ray fluorescence analyzer (Rigaku Corporation), about 20-30 mg of the sample was placed on filter paper, covered with PP film, and subjected to composition analysis. The amount of palladium determined from the XRF analysis results was calculated as the amount of palladium (mass%) relative to 100% mass of the sample particles. The results are shown in Table 5 as "Pd (wt%)".
[0202] [Crystal structure analysis: XRD method] The measurements were carried out in the same manner as in Examples 1 to 3 and Comparative Examples 1 to 3. The results are shown in Table 5 as "crystallite size (nm)". [Median diameter D 50 Measurement method] The measurements were carried out in the same manner as in Examples 1 to 3 and Comparative Examples 1 to 3. The results are shown in "D 50 The values are shown in Table 5 as "(nm)". [Analysis by Raman spectroscopy] The measurements were carried out in the same manner as in Examples 1 to 3 and Comparative Examples 1 to 3. The results are shown in Table 5 as "G / D(au)".
[0203] [Specific surface area measurement: BET method] The specific surface area (m 2 The results were calculated as BET specific surface area (m 2 The results are shown in Table 5 as " / g".
[0204] [Table 5]
[0205] The results of the XRD analysis are shown in Figure 5. Also, Figure 6 shows images of the particles of Examples 4 to 6 obtained with a transmission electron microscope (TEM, manufactured by JEOL Ltd., JEM-1400). From the results shown in Figures 5 and 6, it was confirmed that all of the compounds obtained in Examples 4 to 6 were Pd-molybdenum carbide composites.
[0206] 7 shows an observation image of the particles of Example 4 obtained by a high-resolution transmission electron microscope (HRTEM, manufactured by JEOL Ltd., JEM-ARM300F). From the EDS mapping image, it is considered that the white spherical particles correspond to Pd particles.
[0207] Fig. 8 is a HAADF-STEM image (transmission electron image, JEM-ARM300F, manufactured by JEOL Ltd.) of the particles of Example 4. Fig. 9 is a SEI image (secondary electron image, JEM-ARM300F, manufactured by JEOL Ltd.) of the particles of Example 4. Note that in Figs. 8 and 9, the same Pd particles are indicated by the same type of arrow. From the results shown in FIG. 8 and FIG. 9, it was confirmed that a large number of Pd nanoparticles with a maximum size of about 20 nm were present on the outermost surface of the molybdenum carbide.
[0208] [Preparation of catalytic ink and evaluation of hydrogen evolution activity (2)] Palladium-molybdenum carbide composites 1 to 3 of Examples 4 to 6, commercially available molybdenum carbide of Comparative Example 4, or 4% Pd-KB of Comparative Example 5 were each mixed with 4 mg of Ketjen Black, 2 mg of 5% Nafion dispersion (Fujifilm Wako Pure Chemical Corporation Nafion dispersion solution) and 40 ul of the mixture in 1 ml of ethanol for 1 hour to produce an ink. 20 ul of the resulting ink dispersion was applied to the surface of an electrode, and the surface liquid was naturally dried. The electrode was then transferred to a vacuum dryer and dried at 60°C for 6 hours or more. The hydrogen generation activity of the prepared electrode was evaluated using a three-electrode method. The evaluation conditions were an LSV method with a scan voltage range of -0.3V to 0V and a scan speed of 5mV / S. Current density 10mA / cm 2 Overpotential (mV) at 0.3V, current density (mA / cm 2 ) are shown in Table 6.
[0209] [Table 6]
[0210] (Example 7: Synthesis of nickel hydroxide-molybdenum carbide composite 1) 100 mg of the molybdenum carbide of Example 2 was dispersed in 40 ml of pure water by ultrasonic waves for 30 minutes to obtain a dispersion. 3 COO) 2 4H 2 O), urea 320 mg (Kanto Chemical Co., Ltd., NH 2 CONH 2 The dispersion was added to the above solution with stirring and kept at 85°C for 3 hours, after which the precipitate in the dispersion was collected using a centrifuge, ultrasonically washed three times with water, and dried in a vacuum to obtain Ni(OH) 2A modified molybdenum carbide powder (nickel hydroxide-molybdenum carbide composite 1) was obtained.
[0211] Comparative Example 6 For commercially available molybdenum carbide (manufactured by Kojundo Chemical Laboratory Co., Ltd.), the Ni(OH) 2 The composite was evaluated in the same manner as for the molybdenum-carbide composite 1. The results are shown in Table 8.
[0212] [Table 7]
[0213] In Table 7, "Mo 2 "C-6" indicates the molybdenum carbide of Example 2.
[0214] <Evaluation> Nickel hydroxide-molybdenum carbide composite 1 of Example 7, Comparative Example 6 The following evaluations were carried out on commercially available molybdenum carbides.
[0215] [XRF analysis] Using a Primus IV X-ray fluorescence analyzer (Rigaku Corporation), approximately 20-30 mg of the sample was placed on filter paper, covered with PP film, and the composition was analyzed. 。
[0216] [Crystal structure analysis: XRD method] Measurements were carried out in the same manner as in Examples 1 to 3 and Comparative Examples 1 to 3. The results are shown in Table 8 as "crystallite size (nm)". [Median diameter D 50 Measurement method] The measurements were carried out in the same manner as in Examples 1 to 3 and Comparative Examples 1 to 3. The results are shown in "D 50 The values are shown in Table 8 as "(nm)". [Analysis by Raman spectroscopy] The measurements were carried out in the same manner as in Examples 1 to 3 and Comparative Examples 1 to 3. The results are shown in Table 8 as "G / D(au)".
[0217] [Specific surface area measurement: BET method] The specific surface area (m 2 The results were calculated as the BET specific surface area (m 2 The results are shown in Table 8 as " / g".
[0218] [Table 8]
[0219] The results of the XRD analysis are shown in Figure 10. Figure 11 shows an observation image of the particles of Example 7 obtained by a transmission electron microscope (TEM). The results shown in Figure 11 show that, compared with the TEM photograph of the molybdenum carbide in Figure 3, Ni(OH) 2 It was confirmed that nanosheets were produced.
[0220] [Preparation of catalytic ink and evaluation of oxygen generation activity] Nickel hydroxide-molybdenum carbide composite 1 of Example 7, Comparative Example 6 Ink was prepared by ultrasonically dispersing 4 mg of any of the commercially available molybdenum carbides, 2 mg of Ketjen Black, and 40 ul of 5% Nafion dispersion (Fujifilm Wako Pure Chemical Corporation Nafion dispersion solution) in 1 ml of ethanol for 1 hour. 20 ul of the resulting ink dispersion was applied to the electrode surface, and after the surface liquid was naturally dried, the electrode was transferred to a vacuum dryer and dried at 60°C for 6 hours or more. The hydrogen generation activity of the prepared electrode was evaluated using a three-electrode method. The electrolyte was a 1.0 Mol / L potassium hydroxide solution (Kanto Chemical Co., Ltd., Potassium hydroxide solution). The evaluation conditions were an LSV method with a scan voltage range of 1.0 V to 1.8 V and a scan speed of 5 mV / S. Current density 10 mA / cm 2 Overpotential (mV) at 1.8 V, current density (mA / cm 2 ) are shown in Table 9.
[0221] [Table 9]
[0222] The configurations and combinations thereof in each embodiment are merely examples, and additions, omissions, substitutions, and other modifications of the configurations are possible without departing from the spirit of the present invention. Furthermore, the present invention is not limited to each embodiment, but is limited only by the scope of the claims.
Claims
1. M.O. 2 The molybdenum carbide has a C crystal structure, a carbon content of 6% or more relative to the total mass (100% by mass) of the molybdenum carbide, and a specific surface area measured by the BET method of 50 to 2000 m 2 / g, and carbon-derived graphite band G and diamond band D are present as measured by Raman spectroscopy.
2. 2. The molybdenum carbide according to claim 1, wherein the ratio (G / D) of the carbon-derived graphite band G to the diamond band D is 0.75 or more.
3. Median diameter D calculated by dynamic light scattering method 50 The molybdenum carbide according to claim 1 , wherein the average particle size is 1000 nm or less.
4. 2. The molybdenum carbide according to claim 1, having an average crystallite size of 50 nm or less, determined from a peak at 2θ=39.4±0.5° in a profile obtained by X-ray diffraction measurement.
5. A hydrogen generation catalyst comprising the molybdenum carbide of claim 1.
6. A hydrogen generation catalyst ink comprising the molybdenum carbide according to claim 1 and a solvent.
7. A composite of noble metal particles having an average particle size of 20 nm or less and the molybdenum carbide according to claim 1.
8. 8. The composite of claim 7, wherein the precious metal particles are palladium particles.
9. The composite of claim 8 , wherein the palladium particles comprise aggregates of palladium atoms not having a crystalline structure.
10. A hydrogen generation catalyst comprising the composite of claim 7.
11. A hydrogen generation catalyst ink comprising the composite according to claim 7 and a solvent.
12. A hydrogen generation catalyst ink described in claim 6 or 11, further containing a conductive material.
13. A hydrogen generation catalyst ink described in claim 6 or 11, further containing a polymer electrolyte.
14. A composite of at least one transition metal species selected from the group consisting of transition metals and transition metal compounds and the molybdenum carbide according to claim 1.
15. The composite with molybdenum carbide according to claim 14, wherein the transition metal species is at least one selected from the group consisting of nickel and nickel compounds.
16. An oxygen evolution catalyst comprising the composite of claim 14.
17. An oxygen generating catalyst ink comprising the composite of claim 14 and a solvent.
18. The oxygen generating catalyst ink according to claim 17, further comprising a conductive material.
19. The oxygen generating catalyst ink according to claim 17, further comprising a polyelectrolyte.
20. A method for producing molybdenum carbide, comprising calcining molybdenum trioxide containing α-crystals having an average crystallite size of 50 nm or less and carbon in the presence of at least one inorganic compound selected from the group consisting of inorganic salts and inorganic hydroxides.
21. The method for producing molybdenum carbide according to claim 20, wherein the inorganic compound is at least one selected from the group consisting of sodium compounds and potassium compounds.
22. The method includes a step of mixing molybdenum carbide and a precious metal solution, The molybdenum carbide is Mo 2 The molybdenum carbide has a C crystal structure, a carbon content of 6% or more relative to the total mass (100% by mass) of the molybdenum carbide, and a specific surface area measured by the BET method of 10 to 2000 m 2 / g, and a carbon-derived graphite band G and a diamond band D are present as measured by Raman spectroscopy.
23. Mixing molybdenum carbide with a transition metal compound solution, The molybdenum carbide has a Mo2C crystal structure, a carbon content of 6% or more relative to the total mass (100 mass%) of the molybdenum carbide, and a specific surface area measured by the BET method of 10 to 2000 m 2 / g, and a carbon-derived graphite band G and a diamond band D are present as measured by Raman spectroscopy.
Citation Information
Patent Citations
Production of carbide of heavy metals having a high specific surface area
JP1991501721A
Hydrogen generating electrode
JP2001234380A
Metal fine grain coated with carbon and redox type capacitor using the fine grain as electrode material
JP2006063403A
Method for manufacturing an ion-containing support
JP2013539718A
Method for producing molybdenum carbide granulated powder and molybdenum carbide granulated powder
WO2012169260A1
